The Role of Innovation Activities on Brand Equity and Brand Performance: The Moderating Effects of Economic Benefit - Pham, Thi Minh Ly; Le, Gia-Phuc; Tran, Cong-Duc; Mi Le, Pham Tra (Transformations In Business & Economics, 2024)
Although the link between innovation and brand performance has been studied, the impact of various dimensions of innovation activities on brand performance remains under explored, with inconclusive findings. This study aims to overcome these shortcomings and contribute to the literature by investigating the influence of brand innovation activities (processes, products, marketing, and retail stores) on brand equity (measured by customers’ affective and cognitive mindsets) and brand performance in Vietnam. This study also examines the moderating effects of boundary conditions, including hedonic/utilitarian factors and economic benefits. Findings from the partial least squares structural equation modelling demonstrated that different types of brand innovation activities positively influence brand love, brand knowledge, and, subsequently, brand performance. The results also validated the positive synergistic interaction between economic benefits and brand love in influencing customer purchase intentions.